Analysis of the thermal conditions of pulse impact avalanche transit-time diodes - M.S. Sorokin; A.V. Arkhipov (Журнал нано- та електронної фізики)
The nonstationary problem of the thermal process for the pulse mode of impact avalanche transit-time diodes is solved. The one-dimensional thermal model of such diodes, which takes into account the heterogeneity of the thermal power distribution and the heat spreading along the heat sink in the operating temperature range, is considered. The numerical calculation results of the average temperature of the active layer and the thermal resistance on the pulse parameters, as well as on the geometric and thermophysical diode parameters, are presented.